Narrative innovation in life design counseling: The case of Ryan - Cardoso, Paulo (2014)
The main aim of this research is to study the patterns of narrative change in a case of life design counseling (LDC). The innovative moments coding system (IMCS) was used to conduct an intensive analysis of the career counseling sessions. This coding system is grounded in a narrative conception of the self, and suggests that narrative change results from the elaboration and development of narrative exceptions to a client's core problematic self-narrative. The results supports the adequacy of the IMCS to the study of change in career counseling and reveal that the intervention promotes a pattern of change characterized by three types of innovative moments: action, reflection, and protest. The results are discussed taking into account their implications for career counseling theory, research and practice.